MOF-Based Biosensors for the Detection of Carcinoembryonic Antigen: A Concise Review - May R. Ibrahim; Yaser E. Greish (Molecules, 2023)
Cancer has been considered one of the most serious diseases in recent decades. Early diagnosis of cancer is a crucial step for expedited treatment. Ideally, detection of cancer biomarkers, which are usually elevated because of cancer, is the most straightforward approach to detecting cancer. Among these biomarkers, the carcinoembryonic antigen (CEA) is considered one of the most important tumor markers for colorectal cancer. The CEA has also been recognized as a biomarker for other types of cancers, including breast, gastric, ovarian, pancreatic, and lung cancers. Typically, conventional CEA testing depends on immunoassay approaches, which are known to be complex, highly expensive, and time consuming. Accordingly, various types of biosensors have been designed for the detection of cancer biomarkers. The main prerequisites of these biosensors are high sensitivity, fast response, and low cost. Many nanostructures have been involved in the design of biosensors, such as nanoparticles of certain metals and metal oxides that are further functionalized to contribute to the sensing of the biomarkers. Alternatively, metal organic frameworks (MOFs), which are extended crystalline structures comprising metal clusters surrounded by organic linkers, have been shown to be highly promising for the development of biosensors. The 3D structure of MOFs results in a combination of high surface area and high interconnected porosity, which are believed to facilitate their function in the design of a biosensor. This review briefly classifies and describes MOF-based biosensor trials that have been published recently for the aim of detecting CEA.